On Spectrum Estimation of a Clipped Gaussian Random Process - Alekseyev, V. G. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Алексеев. Об оценке спектра квантованного по уровню гауссовского случайного процесса V. Aleksejevas. Apie atsitiktinio Gauso proceso spektro, kvantuoto pagal lygmenį, įvertinimą H